Species-Specific Proteins in the Oviducts of Snail Sibling Species: Proteotranscriptomic Study of Littorina fabalis and L. obtusata - Arseniy A. Lobov (MDPI AG, 2021)
Genus Littorina subgenus Neritrema (Mollusca, Caenogastropoda) includes the “obtusata” group of closely related species (Littorina obtusata and L. fabalis). The anatomy of the adult reproductive system (pallial oviduct) is the only reliable feature used for species identification in females of these species. Reproductive system anatomy and reproduction-associated proteins often diverge between sibling species. Despite being of high evolutionary interest, the molecular basis of this divergence remains poorly understood. We performed proteotranscriptomic comparison of oviducts of L. obtusata and L. fabalis by RNA-seq on Illumina HiSeq 2500 and two-dimensional protein electrophoresis (2D DIGE) with MS/MS identification of the species-specific proteins. The interspecies differences in the oviduct were associated with (1) metabolic proteins reflecting overall physiological differences between L. obtusata and L. fabalis, (2) receptor proteins, and (3) transcripts related to transposable elements (TEs). Various receptors identified may recognize a wide variety of ligands from pathogen-associated molecular patterns to specific carbohydrates on the sperm surface. Therefore, these may participate in immune defense as well as in sperm storage and regulation. Species-specificity of multiple TE sequences (coding for reverse transcriptase and ribonuclease H) may indicate the important role of these genomic elements in the Littorina species divergence, which has not been reported previously.